Update on the mechanism of microglia involvement in post-stroke cognitive impairment - Zeng, Tianxiang; Liu, Jun; Zhang, Wenjun; Yu, Yanyan; Ye, Xinyun; Huang, Qianliang; Li, Peng; Jiang, Qiuhua (Frontiers in Aging Neuroscience, 2024)
Post-stroke cognitive impairment (PSCI) is a clinical syndrome characterized by cognitive deficits that manifest following a stroke and persist for up to six months post-event. This condition is grave, severely compromising patient quality of life and longevity, while also imposing substantial economic burdens on societies worldwide. Despite significant advancements in identifying risk factors for PSCI,research into its underlying mechanisms and therapeutic interventions remains inadequate. Microglia, the brain's primary immune effector cells, are pivotal in maintaining, nurturing, defending, and repairing neuronal function, a process intrinsically linked to PSCI's progression. Thus, investigating microglial activation and mechanisms in PSCI is crucial. This paper aims to foster new preventive and therapeutic approaches for PSCI by elucidating the roles, mechanisms, and characteristics of microglia in the condition.burden. The underlying mechanisms of PSCI remain largely unclear, and effective treatments to halt its progression are still lacking. Research has historically focused on risk factors such as cerebral ischemic injury, neurodegeneration, neuroinflammation, blood-brain barrier (BBB) disruption, and oxidative stress [5][6][7][8][9]. Recently, the role of microglia in PSCI has garnered increasing attention [7]. Microglia, the brain's primary immune and pro-inflammatory cells, are critical to the central nervous system's (CNS) immune response. Evidence suggests that microglia-mediated neuronal damage and dysfunction play a pivotal role in the pathogenesis and progression of PSCI, involving neuropathological changes post-stroke and several signaling pathways implicated in cognitive deficits, such as TLR4, JAK/STAT, Nuclear factor kappa-B (NF-κB), and CX3CR1 [8,[10][11]. Understanding the role and activation mechanisms of microglia in PSCI and exploring intervention strategies targeting these mechanisms are crucial. This article reviews the activation mechanisms of microglia and their impact on the prognosis of PSCI, offering new insights into the prevention and treatment of PSCI.